EMPOWERING READING COMPREHENCY UNLEASHING HIGH-ORDER THINKING SKILL (HOTS) STRATEGIES IN KURIKULUM MERDEKA FOR ELEVENTH GRADERS AT SMA SWASTA PEMBDA 1 GUNUNGSITOLI - Marunduri, Suci Wahyuni; Sipayung, Kammer Tuahman; Sinambela, Erika (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2024)
The purpose of this study aims to explore (1) the implementation of HOTS strategies in teaching reading comprehension on Kurikulum Merdeka and (2) to know the students’ responses towards the implementation of HOTS in the eleventh grade of SMA Swasta Pembda 1 Gunungsitoli. This research is a descriptive qualitative with 76 eleventh-grade students and two EFL teachers as subjects of the research. Data was collected from observation, interviews, and questionnaires Two teachers were interviewed and students in two classes each received a questionnaire. The collected data was processed and analysed to provide answers to the research questions. Following that, a descriptive data interpretation is given. Despite the improvements needed, both fostered positive learning environments. Questionnaire analysis revealed 68% of students' positivity towards HOTS strategies, calling for varied problem-solving approaches and alignment of teaching strategies with student interests and motivation. Students favoured group projects and reading analysis but highlighted motivation, learning facility, and reading material adequacy. The implementation of HOTS in teaching reading comprehension at SMA Swasta Pembda 1 Gunungsitoli reflects the efforts by both teachers to integrate critical thinking, collaboration, and creativity by (1) choosing suitable texts, (2) questioning the students, (3) asking the author’s point of view from the texts, (4) gathering information, (5) mind mapping, (6) group discussion, and (7) guessing inferring meaning. Teacher 1 emphasized comprehensive HOTS integration, while Teacher 2 showed mastery of the material with management challenges. A collaborated effort between teachers and students is pivotal for optimizing HOTS and enhancing student outcomes. However, challenges related to students' motivation for reading, the utilization of school facilities, and the need for appropriate reading materials remain areas for improvement in enhancing students' engagement and comprehension in reading comprehension activities under the HOTS framework.